2000
DOI: 10.2307/1506864
|View full text |Cite
|
Sign up to set email alerts
|

A Note on the Analysis of Gilded Metal Embroidery Threads

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. This content downloaded from 128.235.251.160 on Mon, Summary-The chemical composition of metal decorations in old textile objects must be known in order to enable the best poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 1 publication
0
21
0
Order By: Relevance
“…According to written sources [5,18,19], the cut strips are early times threads dated from the 13th century onwards, uneven in size and quality and of variable thickness, obtained by cutting a gilt metal sheet. The flattened strips, dated from the 14th century Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to written sources [5,18,19], the cut strips are early times threads dated from the 13th century onwards, uneven in size and quality and of variable thickness, obtained by cutting a gilt metal sheet. The flattened strips, dated from the 14th century Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, EDS may sometimes give erroneous results. It was observed that the gold concentrations resulted for the gold coating and reported in previous publications are often too low depending on the high accelerating voltage used (usually 20-30 keV in practice), and thus incorrect [5,6].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…We believe that most of the threads were manufactured abroad. Most analyses have been performed with a Jeol JSM-840A scanning electron microscope equipped with a Link-EDS unit for X-ray microanalysis at 20kV (SEM/EDS), occasionally also by Auger electron spectroscopy (AES) [1,2].…”
Section: The Materialsmentioning
confidence: 99%
“…Material has been obtained from the church and Swedish collections, and SEM/EDS (scanning electron microscopy with energy-dispersive X-ray microanalysis) analyses have been undertaken. A first report was given at the 1999 ICOM-CC conference in Lyon [1], followed by a note on the analysis of gilded metal embroidery threads [2].…”
Section: Introductionmentioning
confidence: 99%